The effects of age on health-related quality of life in cancer populations: A pooled analysis of randomized controlled trials using the European Organisation for Research and Treatment of Cancer (EORTC) QLQ-C30 involving 6024 cancer patients. Issue 18 (December 2015) - Quinten, Chantal; Coens, Corneel; Ghislain, Irina; Zikos, Efstathios; Sprangers, Mirjam A.G.; Ringash, Jolie; Martinelli, Francesca; Ediebah, Divine E.; Maringwa, John; Reeve, Bryce B.; Greimel, Eva; King, Madeleine T.; et al.
Abstract: Background: Cancer incidence increases exponentially with advancing age, cancer patients live longer than in the past, and many new treatments focus on stabilizing disease and HRQOL. The objective of this study is to examine how cancer affects patients' HRQOL and whether their HRQOL is age-dependent. Methods: Data from 25 EORTC randomized controlled trials was pooled. EORTC QLQ-C30 mean scores for the cancer cohort and five general population cohorts were compared to assess the impact of cancer on patients' HRQOL. Within the cancer cohort, multiple linear regressions (two-sided level P-value = 0.05 adjusted for multiple testing.) were used to investigate the association between age and HRQOL, adjusted for gender, WHO performance status (PS), distant metastasis and stratified by cancer site. A difference of 10 points on the 0–100 scale was considered clinically important. Results: Cancer patients generally have worse HRQOL compared to the general population, but the specific HRQOL domains impaired vary with age. When comparing the cancer versus the general population, young cancer patients had worse financial problems, social and role functioning, while the older cancer groups had more appetite loss. Within the cancer cohort, HRQOL was worse with increasing age for physical functioning and constipation, and better with increasing age for social functioning, insomnia and financial problems (all p < 0.05). Conclusion: HRQOL is impaired in cancer patients compared to the general population, but the impact on specific HRQOL domains varies by age. Within the cancer population, some HRQOL components improve with age while others deteriorate. Optimal care for older cancer patients should target HRQOL domains most relevant to this population. Highlights: Data from 25 EORTC trials, including 6024 patients were pooled for this analysis Cancer patients have worse HRQOL compared to the general population, but the HRQOL domains that are impaired vary by age. Cancer patients report better HRQOL with increasing age for social and role functioning and financial problems. Cancer patients report worse HRQOL with increasing age for physical and cognitive functioning and constipation. HRQOL burden changed with age for each cancer site, but the magnitude and size differed between cancer sites.